Job satisfaction and organisational commitment: An Empirical Evidence in Small and Medium Size Enterprises in Cameroon. - Fon Tamandjong , Georges; Douanla Jean , Christian; Innocent, Essomme (Revue Internationale des Sciences de Gestion, 2020)
The main purpose of this study was to investigate the influence of job satisfaction on the commitment of employees of small and medium size enterprises (SMEs) in Cameroon for their organisations. General job satisfaction was used as dependent variable then the three foci of commitment were used as dependent variables. Three hypotheses were formulated based on the link of the concepts in literature. The data for the study was collected using questionnaire on a sample size of 1556 employees of SMEs in Cameroon. The data was analysed using Pearson correlation analyses and regression analyses. The result reveals that job satisfaction has a positive and significant influence on the affective, normative and continuance commitment of employees of SMEs for their organisations. From this result it was recommended that the management of SMEs in Cameroon should always bring up strategies to keep their employees satisfied to their jobs so as to be committed.